Escala para evaluar la experiencia espiritual diaria en una muestra de jóvenes de Bogotá, Colombia: análisis psicométrico - Osorio Castaño, César Augusto (2024)
The psychometric properties of the Scale to Evaluate the Daily Spiritual Experience (DSES) of Underwood and Teresi (2002) were analyzed with a sample of 603 Colombian youth aged between 18 and 24 years (M = 20.77; SD = 1.94), 67.5% were women and 32.3% men. The exploratory factor analysis was performed, that confirmed that the scale is one-dimensional, the goodness-of-fit indexes of the confirmatory factor analysis (CMIN / DF = 2.7; GFI = .95; IFI = .98; TLI = .98; CFI = .98; RMSEA = .05) and internal consistency (alpha = .94 and McDonald’s ω = .95). The fit of the items was evaluated through an analysis with the Rasch model and evidence of convergent and divergent validity was obtained. The DSES was shown as a valid and reliable scale.